Enhancing lignin degradation by Mn2+ ion supplementation to assist enzymatic hydrolysis of cellulose in a two-stage pretreatment of bamboo - Jian, Liu; Lihui, Gan; Minnan, Long (International Journal of Agricultural and Biological Engineering, 2017)
Abstract: It is of great significance to reveal a key agent to improve the efficiency of conversion of lignocellulosic biomass to fermentable sugars for the production of bioethanol. This study investigated a two-stage pretreatment of bamboo comprising a microbial treatment using Ceriporiopsis sp. followed by a hydrothermal treatment to facilitate the process with Mn2+ as an accelerator. The effects of Mn2+ nutritional addition on ligninolytic activity, lignin degradation, total weight loss, pulp yield, sugar yield and sugars in the soluble fraction were examined. The results showed that the time required for the incubations supplemented with Mn2+ to achieve sufficient lignin degradation and sugar yield from both the pulp and soluble fractions was significantly shortened, whereas all three ligninolytic activities were significantly decreased. The enzyme activity varied according to the presence of Mn2+, although the amount and species of the expressed protein are similar. Considering the cost, microbial treatment with a one-time fed-batch supply of metal nutrition (MnSO4) was the most preferable contribution to hydrothermal pretreatment, resulting in 19.7% lignin degradation, 66.7% pulp yield and 26.1% sugar yield over a period of 21 d. It was proven that microbial treatment by solid state incubation with Mn2+ nutrition has the potential to be a low-cost, environmentally friendly alternative to chemical approaches.Keywords: hydrolysis, fungi, Mn2+ ion, pretreatment, bamboo, Ceriporiopsis sp.DOI: 10.3965/j.ijabe.20171003.2991Citation: Liu J, Gan L H, Long M N. Enhancing lignin degradation by Mn2+ ion supplementation to assist enzymatic hydrolysis of cellulose in a two-stage pretreatment of bamboo. Int J Agric & Biol Eng, 2017; 10(3): 175–184.